Anti-corruption clauses and public procurement: special reference to the case of business consortiums - Reaño Peschiera, José Leandro (2024)
This article examines the inclusion of anticorruption clauses in Peruvian state contracts, introduced following the Lava Jato case in 2017.These clauses seek to ensure integrity by requiring contractors to declare that they have not engaged in corrupt acts and to adopt preventive measures.However, their application in contracts with consortia generates conflicts, since each member must assume joint liability for violations by others.Differences are explored between concession contracts, which require a Special Purpose Vehicle (SPV), and license contracts, where the consortium maintains its legal autonomy, highlighting the need for a consistent application of these clauses to respect the associative structure and liability rules.